Does telework weaken urban structure–travel relationships? - Erik Elldér (Journal of Transport and Land Use)
This paper investigates whether urban structure influences daily travel behavior differently when people telework in urban contexts. Regression models are applied to address whether and to what extent travel is associated with various measures of urban structure and key destination accessibility relative to the home location in Gothenburg, Sweden. The analysis treats groups of workers defined by teleworking practices. Micro-level data from the Swedish National Travel Survey 2011 capture individual travel behavior, while Swedish register data on the location of all firms and individuals combined with a GIS-based tool that measures travel times by car or public transport capture urban structure. Results indicate that telework weakens the relationship between urban structure and travel. Regression models of travel distance and time as functions of various geographical aspects of residential location display a much better fit for those not teleworking regularly. Telework allows various mobility strategies that together foster more spatially heterogeneous daily travel behavior, more dependent on personal attributes than on the home location relative to the workplace. Planners and policymakers should monitor whether the number of teleworkers continues to increase. If so, traditional distance- and location-based models and policies for predicting and planning transport may prove less accurate and effective than currently assumed.